2020
DOI: 10.1186/s13024-020-00364-w
|View full text |Cite
|
Sign up to set email alerts
|

α-Synucleinopathy associated c-Abl activation causes p53-dependent autophagy impairment

Abstract: Background: Studies link c-Abl activation with the accumulation of pathogenic α-synuclein (αS) and neurodegeneration in Parkinson's disease (PD). Currently, c-Abl, a tyrosine kinase activated by cellular stress, is thought to promote αS pathology by either directly phosphorylating αS or by causing autophagy deficits. Methods: αS overexpressing transgenic (Tg) mice were used in this study. A53T Tg mice that express high levels of human mutant A53TαS under the control of prion protein promoter. Two different app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 75 publications
(131 reference statements)
3
39
0
Order By: Relevance
“…These results agree with a recent report showing that DMSO does not trigger apoptosis or senescence in the substantia nigra cells, neither elicits changes in the cytoskeleton or density of dendritic spines [38] or behavioral alterations [37]. Other authors that used 100% DMSO also do not report damage or altered function in vivo [77][78][79][80]. In contrast, other studies have reported that DMSO is toxic in cell cultures.…”
Section: Discussionsupporting
confidence: 91%
“…These results agree with a recent report showing that DMSO does not trigger apoptosis or senescence in the substantia nigra cells, neither elicits changes in the cytoskeleton or density of dendritic spines [38] or behavioral alterations [37]. Other authors that used 100% DMSO also do not report damage or altered function in vivo [77][78][79][80]. In contrast, other studies have reported that DMSO is toxic in cell cultures.…”
Section: Discussionsupporting
confidence: 91%
“…AMPK exerts a neuroprotective effect against various neurodegenerative injury, and reduced AMPK expression leads to neurodegeneration. In contrast, AMPK activation regulates neurodegeneration [ 35 , 36 , 52 54 ]. Activated AMPK regulates aberrant brain metabolism and reduces insulin resistance [ 14 – 16 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD) is a severe neurodegenerative disorder which is categorised by bradykinesia (slow movement), postural instability, muscular rigidity and resting tremors [1,2]. Many PD cases are from an obscure cause, though some are known to be caused by missense mutations in the α-synuclein gene [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Rescue of Bax induced block of cell growth by untagged α-synuclein (1-3 copies) on GAL1p and α-synuclein-HA (1-3 copies) on MET25p(A) Growth on solid agar minimal medium plates of yeast transformants bearing one(1), two(2) or three (3) copies of the α-synuclein gene under the control of MET25 promoter (MET-α-syn-HA) and Bax gene under the control of GAL1 promoter (Bax). (B) Growth of yeast strains containing 1, 2 and 3 copies of α-synuclein-HA (MET25p) with a copy of Bax in a minimal liquid medium (SG + 0.1% glucose) along with controls.…”
mentioning
confidence: 99%